A Pilot Study on Environmental Factors, Production Performance and Recycling Practices in Cement Plants in Pakistan - Larik, Temoor Abbas; Yusri Yusof; Shaikh, Faheemllah; Khan, Zohaib (Journal of Advanced Mechanical Engineering Applications, 2026)
The cement manufacturing industry is highly environmentally intensive due to its energy consumption, clinker production, and greenhouse gas emissions. Despite increasing sustainability pressures, there is limited empirical evidence on how environmental practices and recycling initiatives influence production performance, particularly in developing contexts such as Pakistan. Recycling and the use of industrial byproducts are considered key strategies for improving resource efficiency and reducing environmental impact. However, the effectiveness of these practices in enhancing operational performance remains insufficiently understood. This study aims to assess the relationships between environmental practices, recycling adoption, and production performance in cement plants. Prior to full-scale analysis, a pilot study with 100 respondents was conducted to evaluate the measurement instrument's reliability and to conduct correlation analyses. The results demonstrate excellent internal consistency across all constructs. The Cronbach’s Alpha values range from 0.897 to 0.917, exceeding recommended thresholds. Key constructs such as Regulatory Framework (α = 0.905), Waste Management Regulations (α = 0.906), Cost Efficiency (α = 0.906), and Impact on Cement Strength (α = 0.917) exhibited particularly strong reliability. Descriptive findings indicated moderate response variability, with most standard deviations ranging from 0.50 to 0.80, suggesting meaningful differentiation among respondents. However, correlation analysis suggests a strong positive relationship between environmental practices and production performance, environmental practices and recycling adoption, and recycling adoption and production efficiency within cement plants (r = 0.780, 0.617& r = 0.639, respectively; p = 0.000). Overall, these findings confirm the robustness of the research framework and highlight the interconnected role of environmental orientation, recycling initiatives, and production performance in cement plant operations.